The degradation of oilseed cakes and their effects on the intake and rumen degradability of maize stover given to Ethiopian Menz sheep - Sibanda, S.; Osuji, P.O.; Nsahlai, I.V. (1993)
Six rumen cannulated sheep (26.1 (s.d. 2.24 kg live weight) given maize stover ad libitum were supplemented with either sunflower cake (SFC), decorticated cottonseed (CSC) or noug cakes (NGC) with or without crushed maize grain. The 6x6 Latin-square experiment studied the degradation properties of the oilseed cakes and their effects and that of maize on the degradation of maize, maize stover and the composite diet. Seedcakes differed in the degradability characteristics of dry matter and nitrogen intercept potentially degradable fraction; rate of degradation, and the effective degradability. The pooled sum of the degradabilities of individual ingredients were significantly lower than that of mixed ingredients. The main effects of protein and maize were not significant on the degradation of maize stover. Maize had the tendency to depress the rates of degradation of stover by 0.52 with SFC. Although the protein X maize interaction was not significant on maize stover degradability, it is important to note that maize had the effect of increasing stover degradation rate with CSC and NGC, but a depressing effect with SFC. Hence it was concluded that the carbohydrate effect on roughage degradation rate may vary as function of the difference between the degradation rate of the energy and protein supplement.